Association Between Commute Duration and Sickness Absence in the Context of China: Mechanism and Heterogeneous Effects - Wang, Zicheng; Wu, Qiushi; Guo, Murong (Frontiers in Public Health, 2021)
Background: Most employees in urban China have experienced a heavy commuting burden, which has become an urgent issue that should be solved in the new urbanization strategy process. However, the exploration of the relationship between the commute duration and sickness absence remains scant in China, and no direct discussion has been done to analyze the mechanism linking commute duration and sickness absence. Methods: Using a unique dataset of the 2013 China Matched Employer–Employee Survey, the present study applies a two-level random-intercept Poisson model to explore this association. Results: A long commute is significantly related with increased sickness absence. A longer commute is associated with poorer self-rated health status and a higher degree of psychological depression, and it is also highly related with a decrease in sleeping time. Moreover, an increased commuting duration is associated with lower work effort (working hours). Conclusion: Longer commute duration induces lower productivity through increased sickness absence, and the potential link of commute duration and sickness absence is mainly transmitted through health-related outcomes and work effort.